Mechanisms of cold‐induced immunity in plants. Issue 1 (17th January 2023) - Sasaki, Kentaro; Imai, Ryozo
Abstract: Overwintering plants acquire substantial levels of freezing tolerance through cold acclimation or winter hardening. This process is essential for the plants survival to harsh winter conditions. In the areas where persistent snow cover lasts several months, plants are protected from freezing but are, however, exposed to other harsh conditions, such as dark, cold, and high humidity. These conditions facilitate the infection of psychrophilic pathogens, which are termed "snow molds." To fight against infection of snow molds, overwintering plants develop disease resistance via the process of cold acclimation. Compared with pathogen‐induced disease resistance, the molecular mechanisms of cold‐induced disease resistance have yet to be fully elucidated. In this review, we outline the recent progress in our understanding of disease resistance acquired through cold acclimation.